Natural and fallout radioactivity levels and radiation hazard evaluation in soil samples - Karataşlı M.; Ş, Turhan; Varinlioğlu A.; Yeğingil Z. (Springer Science and Business Media LLC, 2016)
The present study aims to obtain the baseline data on natural and fallout radioactivity and to evaluate radiation hazards caused by ionizing radiation emitted from 226Ra, 232Th, 222Rn, 40K and 137Cs in surface soil samples collected from Mersin province and Akkuyu nuclear power plant region. The activity concentrations of 226Ra, 232Th, 40K and 137Cs were measured using a gamma spectrometer with HPGe detector. The activity concentrations of 226Ra, 232Th, 40K and 137Cs varied from 14.1 ± 0.7 to 65.4 ± 2.9, 12.0 ± 0.8–51.7 ± 2.1, 172.2 ± 15.8–511.1 ± 37.8 and <MDA to 86.2 ± 1.4 Bq kg−1, respectively. The average concentrations of radon in soil and air were estimated as 23.9 kBq m−3 and 76 Bq m−3. The radiological parameters such as absorbed gamma dose rate in outdoor air (DRout), annual effective dose rate from external exposure (E Ext), annual effective dose rate from inhalation of radon (E Inh) and lifetime cancer risk (LTCR) were calculated to evaluate radiological hazards. The average values of DRout, E Ext, E Inh and LTCR were found to be 51 nGy h−1, 62 μSv year−1, 715 μSv year−1 and 2.2 × 10−4, respectively.
Keywords: Fallout radioactivity; Lifetime cancer risk; Soil; Gamma dose rate; Radon; Natural radioactivity; Annual effective dose rate; 13. Climate action; 7. Clean energy